Stress memory induced rearrangements of HSP transcription, photosystem II photochemistry and metabolism of tall fescue (Festuca arundinacea Schreb.) in response to high-temperature stress - Hu, Tao; Liu, Shu-Qian; Amombo, Erick; Fu, Jin-Min (Frontiers in Plant Science, 2015)
When plants are pre-exposed to stress, they can produce some stable signals and physiological reactions that may be carried forward as ‘stress memory’. However, there is insufficient information about is known about plants’ stress memory responses mechanisms. Here, two tall fescue genotypes, heat-tolerant PI 574522 and heat-sensitive PI 512315, were subjected to recurring high-temperature pre-acclimation treatment. Two heat shock protein (HSP) genes, LMW-HSP and HMW-HSP, exhibited transcriptional memory for their higher transcript abundance during one or more subsequent stresses (S2, S3, S4) relative to the first stress (S1), and basal transcript levels during the recovery states (R1, R2 and R3). Activated transcriptional memory from two trainable genes could persist up to 4 days, and induce higher thermotolerance in tall fescue. This was confirmed by greater turf quality and lower electrolyte leakage. Pre-acclimation treatment inhibited the decline at steps of O-J-I-P and energy transport fluxes in active Photosystem II reaction center (PSII RC) for both tall fescue genotypes. The heat stress memory was associated with major shifts in leaf metabolite profiles. Furthermore, there was an exclusive increase in leaf organic acids (citric acid, malic acid, tris phosphoric acid, threonic acid), sugars (sucrose, glucose, idose, allose, talose, glucoheptose, tagatose, psicose), amino acids (serine, proline, pyroglutamic acid, glycine, alanine) and one fatty acid (butanoic acid) in pre-acclimated plants. These discoveries involved in transcriptional memory, PSII RC energy transport and metabolite profiles could provide new insights into the plant high–temperature response process.